(untitled) (Fiep Bulletin - online, 2016)
The nail polishes are organic compounds, it’s mainly principally nitrocellulose, solvent, plasticizer, resin and colorings, constituted by formaldehyde, toluene and lead. Therefore, the constant exposure to this cosmetic (nail polish), for the professionals that use it, can lead to intoxication over time the biological system by solvents present in its composition. Objective: This study aims to check for signs and symptoms of occupational poisoning in manicures. Methodology: The study is conducted epidemiological descriptive type, transversal, quantitative, whose sample consisted of 100 individuals who agreed to participate in the survey, answering to a formulary, which contains objective questions that were used as variables. The information, after compiled, it was presented in tables and graphs simple frequency expressed in numbers and percentages. The ethical aspects have been respected, according to Resolution N° 196/96 (CNS-MS). Results: It showed that 33% of subjects were between 28 and 32 years of age; 55% had 5-10 years of profession; 42% works 8 hours per day; 35% is accustomed to work in weekends. Regarding the signs and symptoms, 70% reported present weakness; 65% blurry vision; 62% dizziness; 25% allergic manifestation; 25% don’t use PPE. Conclusion: The obtained results suggest that, there exist evidences of manifestations of poisoning at the expense of the toluene and the formaldehyde, with reference to the presented symptoms, but without evidences of signs.